Anneal-induced transformation of phase structure, morphology and luminescence of GdPO4:Sm3+ nanomaterials synthesized by a hydrothermal method. Issue 9 (15th February 2017) - Zou, Xiao; He, Lihua; Tan, Dihao; Lei, Fengying; Jiang, Na; Zheng, Qiaoji; Lin, Dunmin; Xu, Chenggang; Liu, Yongfu
Abstract : GdPO4 ·H2 O: x Sm 3+ nanomaterials were synthesized via a facile hydrothermal method and the effects of Sm 3+ concentrations and annealing temperature on the crystal structures, morphologies, and luminescent properties were studied. Abstract : GdPO4 ·H2 O: x Sm 3+ nanomaterials were synthesized via a facile hydrothermal method and the effects of Sm 3+ concentrations and annealing temperature on the crystal structures, morphologies, and luminescent properties were studied. Doping of Sm 3+ exhibited no obvious influence on the crystal structure for the non-annealed samples, which possessed a hexagonal structure and a nanorod shape. Under 401 nm excitation, GdPO4 ·H2 O: x Sm 3+ displays a typical emission band with several peaks at 560, 596, and 640 nm. For the optimal sample of GdPO4 ·H2 O:1.75%Sm 3+, as the annealing temperature was increased from 300 to 800 °C, the compound transformed from GdPO4 ·H2 O with a hexagonal symmetry to anhydrous GdPO4 with a monoclinic symmetry, and the morphologies varied from nanorods to ellipse-like shapes. The length of the nanorods was about 200 nm, whereas the ellipse-like shape exhibited a length of 100 nm and a diameter of 50 nm. The luminescent intensity was enhanced with the increased annealing temperature because the compound transformed from GdPO4 ·H2 O to anhydrous GdPO4 and the nonradiative transition was reduced due to variation in the morphology. Moreover, GdPO4 ·H2 O:1.75%Sm 3+ exhibits paramagnetic performance. In addition, the potential applications in bioimaging and MRI were investigated.